Elaboración de una matriz de toma de decisión para el plan de análisis y control de corrosión en la línea de descarga de pozo en facilidades de producción del campo A (2019)
In the first place, topics related to the production of fluids in the petroleum industry were discussed, the production facilities of the oil industry were also taken into account, focusing on the well discharge lines. The study was carried out only in the well discharge line, which is in charge of transporting the hydrocarbons from the head of the producing well to the entrance of the separators. The design and construction of the matrix that worked as a tool for the development of the project was made. This construction took into account the variable object that is the thickness of the pipe, which was determined from the use of non-destructive tests. Once the data were entered, a pipeline rating was made, which was determined from the degree of thickness wear. This qualification is validated based on the standards generated by the ASME B 31.4 standard. The data provided by the support company was analyzed, and subsequently the respective construction of the graphic behavior was carried out. Finally, the implementation was analyzed using the economic indicator VPN (net present value).